Application of FPGA in the Control System of Volt-boost Static Var Generator - QIU Yuefeng; ZHANG Dinghua; LAN Deshao; TANG Jianyu (Kongzhi Yu Xinxi Jishu)
It proposes and finishes a new scheme design that the FPGA is applied to the control flow of volt-boost SVG(static var generator). The design takes full advantages of FPGA in parallel computing and data handling to implement the base calculation of control software, so that the performance burden of multichannel high-precision calculation is decreased for DSP and the compensation of SVG is enhanced. Feasibility of the scheme has been proved.